GE_GERICHTE P/13762/2012 vom 20. Januar 2014 - GE Cour de justice (2014)
DISPOSITIONS PÉNALES DE LA LETR; SÉJOUR ILLÉGAL; ENTRÉE ILLÉGALE; ACTE D'ACCUSATION | LEtr.115.1.a; LEtr.115.1.b; CPP.325; CPP.389; CP.14; LAsi.42